Prognostic and Predictive Factors in Elderly Patients With Glioblastoma: A Single-Center Retrospective Study - Liu, Jinghui; Li, Chen; Wang, Yuan; Ji, Peigang; Guo, Shaochun; Zhai, Yulong; Wang, Na; Lou, Miao; Xu, Meng; Chao, Min; Jiao, Yang; Zhao, Wenjian; et al. (Frontiers in Aging Neuroscience, 2022)
Glioblastoma (GBM) is the most common primary malignant intracranial tumor and the median age at diagnosis is 65 years. However, elderly patients are usually excluded from clinical studies and age is considered as an independent negative prognostic factor for patients with GBM. Therefore, the best treatment method for GBM in elderly patients has remained controversial. Elderly GBM patients (≥60 years old) treated between January 2015 and December 2019 were enrolled in this study. Medical records were reviewed retrospectively, and clinicopathological characteristics, treatments, and outcomes were analyzed. A total of 68 patients were included, with a median age of 65.5 years (range:60–79). The median preoperative Karnofsky performance scale (KPS) score was 90 (range 40–100) and median postoperative KPS score was 80 (range 0–90). Univariate analysis results showed that age, gender, comorbidities, preoperative KPS<90 and MGMT promoter methylation were not significantly associated with PFS and OS. On the other hand, total resection, postoperative KPS≥80, Ki67>25%, and Stupp-protocol treatment were significantly associated with prolonged PFS and OS. Moreover, multivariate analysis found that postoperative KPS≥80, total resection, and Stupp-protocol treatment were prognostic factors for PFS and OS. The findings of this study have suggested that, on the premise of protecting function as much as possible, the more aggressive treatment regimens may prolong survival for elderly patients with GBM. However, further studies, particularly prospective randomized clinical trials, should be conducted to provide more definitive data on the appropriate management of elderly patients, especially for patients with MGMT promoter methylation.